Przestrzeń w grze wideo Dark Souls jako narzędzie do kreowania światoopowieści - Mróz, Michał (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2023)
The aim of the article is to analyze how space in the video game “Dark Souls” affects various aspects of the interactive text, especially its plot and gameplay. The author focuses on the role of space in the narrative structure of the game, using storyworld concept, analyzing architecture, and the importance of items and their descriptions in constructing the narrative, which is crucial for the reconstruction of story points and also a proper understanding of the game’s religious motives. He goes on to focus on the storyworld events generated by gameplay, describing how it is influenced by space arrangement.